Potensi Geografis Tanaman Pangan Sulawesi Selatan dalam Mendukung Kedaulatan Pangan Nasional - Kaslam K (UNIVERSITAS NEGERI MAKASSAR, 2023)
AbstractIndonesia is still listed as an importing country for food, including rice. In fact, South Sulawesi, which is known as a food barn area, should have a contribution to national food sovereignty, given the large geographical potential in the development of food crops. The purpose of this study is to map the geographic potential of food crops in South Sulawesi in supporting national food sovereignty. This study uses a quantitative survey method to measure the potential of food crops in each district in South Sulawesi. As a result, the geographical potential of South Sulawesi strongly supports the creation of national food sovereignty. The harvested area of rice crops in South Sulawesi in 2020 is 978,192.54 ha, supported by irrigation from rivers and dams, making this province worthy of being called a national rice barn. Rice production is the mainstay product of the majority in South Sulawesi, with 4,670,874.06 tons produced in 2020, making South Sulawesi fourth nationally.AbstrakIndonesia masih tercatat sebagai negara pengimpor bahan pangan, termasuk beras. Padahal, Sulawesi Selatan yang dikenal sebagai daerah lumbung pangan, seharusnya memiliki kontribusi bagi kedaulatan pangan nasional, mengingat potensi geografis yang besar dalam pengembangan tanaman pangan. Tujuan penelitian ini adalah untuk memetakan potensi geografis tanaman pangan di Sulawesi Selatan dalam mendukung kedaulatan pangan nasional. Penelitian ini menggunakan metode survei kuantitaif untuk mengukur potensi tanaman pangan yang ada di setiap kabupaten di Sulawesi Selatan. Hasilnya, potensi geografis Sulawesi Selatan sangat mendukung terciptanya kedaulatan pangan nasional. Luas panen tanaman padi di Sulawesi Selatan pada tahun 2020 seluas 978.192,54 ha yang ditunjang dengan irigasi dari sungai dan bendungan menjadikan provinsi ini layak dikatakan sebagai lumbung padi nasional. Produksi padi merupakan produk andalan mayoritas di Sulawesi Selatan, sebanyak 4.670.874,06 ton yang diproduksi pada tahun 2020, menjadikan Sulawesi Selatan urutan keempat secara nasional.